A murine model demonstrates capsule-independent adaptive immune protection in survivors of Klebsiella pneumoniae respiratory tract infection - Joy Twentyman; Catherine Morffy Smith; Julia S. Nims; Aubree A. Dahler; David A. Rosen (The Company of Biologists, 2020)
Klebsiella pneumoniae represents a growing clinical threat, given its rapid development of antibiotic resistance, necessitating new therapeutic strategies. Existing live-infection models feature high mortality rates, limiting their utility in the study of natural adaptive immune response to this pathogen. We developed a preclinical model of pneumonia with low overall mortality, in which previously exposed mice are protected from subsequent respiratory tract challenge with K. pneumoniae. Histologic analyses of infected murine lungs demonstrate lymphocytic aggregates surrounding vasculature and larger airways. Initial exposure in RAG1 knockout mice (lacking functional B and T cells) failed to confer protection against subsequent K. pneumoniae challenge. While administration of isolated K. pneumoniae capsule was sufficient to provide protection, we also found that initial inoculation with K. pneumoniae mutants lacking capsule (Δcps), O-antigen (ΔwecA) or both conferred protection from subsequent wild-type infection and elicited K. pneumoniae-specific antibody responses, indicating that non-capsular antigens may also elicit protective immunity. Experiments in this model will inform future development of multivalent vaccines to prevent invasive K. pneumoniae infections.